Challenging workplace bullying: the role of social work leadership integrity. Issue 4 (1st October 2016) - Webster, Mike
ABSTRACT: This research paper explores ethical and moral outrage provoked by the phenomenon of workplace bullying in social work agencies. Its aim is to identify formal and organic actions, motivated by leadership integrity, designed to implement organisational social justice. The paper presents two case studies which illustrate contrasting approaches to the phenomenon. The first depicts management collusion with intimidatory behaviour in which the burden of evidence was placed on the victim even while still interacting with the perpetrator. In the second, a self-efficacious team leader proactively confronted bullying by asking questions. Failure of leadership to address bullying is evaluated in the context of the International Federation of Social Work's recognition of management in 2004 as 1 of 13 core purposes of the profession [Sewpaul, Vishanthie, and David Jones. 2005. "Global Standards for the Education and Training of the Social Work Profession." International Journal of Social Welfare 14 (3): 218–230]. The 12 remaining purposes express social work's commitment to social justice as the profession's defining value [Ife, Jim. 2010. "Human Rights and Social Justice." In Ethics and Value Perspectives in Social Work, edited by M. Gray and S. A. Webb, Chap. 13, 148–159. Basingstoke: Palgrave Macmillan]. This paper argues that the prime function of social work leadership is to implement organisational social justice, and concludes that socially just leadership is eminently practicable.